2017
DOI: 10.1021/acsami.7b10442
|View full text |Cite
|
Sign up to set email alerts
|

LiMn2O4 Surface Chemistry Evolution during Cycling Revealed by in Situ Auger Electron Spectroscopy and X-ray Photoelectron Spectroscopy

Abstract: This work utilizes in situ electrochemical and analytical characterization during cycling of LiMnO (LMO) equilibrated at different potentials in an ultrahigh vacuum (UHV) environment. The LMO reacts with organic molecules in the vacuum to form a high surface concentration of LiCO (≈50% C) during initial charging to 4.05 V. Charging to higher potentials reduces the overall LiCO concentration (≈15% C). Discharging to 3.0 V increases the LiCO concentration (≈30% C) and over discharging to 0.1 V again reduces its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 50 publications
3
19
0
Order By: Relevance
“…The surface oxidation states of Mn were then examined by X-ray photoelectron spectroscopy (XPS) with a shallow detection scale (<3 nm). Figure 6c shows Mn 2p 1/2 and 2p 3/2 peaks of two samples at 640.9 and 653.1 eV, consistent with the data reported before 55,56 . Further fitting results showed that Mn 4+ respectively occupied 47% and 59% of the LMO and LR-LMO sample surfaces (Fig.…”
Section: Resultssupporting
confidence: 90%
“…The surface oxidation states of Mn were then examined by X-ray photoelectron spectroscopy (XPS) with a shallow detection scale (<3 nm). Figure 6c shows Mn 2p 1/2 and 2p 3/2 peaks of two samples at 640.9 and 653.1 eV, consistent with the data reported before 55,56 . Further fitting results showed that Mn 4+ respectively occupied 47% and 59% of the LMO and LR-LMO sample surfaces (Fig.…”
Section: Resultssupporting
confidence: 90%
“…We hypothesize that heterogeneously delithiating a single plane can induce a larger effect, than was previously calculated for homogeneous delithiation by Wu and Zhang . Results of Li NMR indicate that these point defects are heterogeneously distributed, suggesting that this hypothesis is reasonable. Calculations similar to those in Ref.…”
Section: Resultsmentioning
confidence: 48%
“…However, processes inducing capacity fade are many and often interrelated . For example, mechanical degradation, surface reactions, gas evolution, loss of percolation, Li interactions with inactive components, corrosion, and their interactions have been associated with capacity fade . Mechanical degradation and fracture has received considerable attention, as particle fracture can lead to electronic and/or ionic isolation of a portion of the active material .…”
Section: Introductionmentioning
confidence: 99%
“…Such reactions were observed to a much higher extend by the authors using model cells assembled within a glovebox and transferred to an UHV system. 18,34…”
Section: C1smentioning
confidence: 99%